2016
DOI: 10.1590/s0100-204x2016000300007
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade da fauna edáfica e epigeica de invertebrados em consórcio de mandioca com adubos verdes

Abstract: Resumo -O objetivo deste trabalho foi avaliar a densidade e a diversidade da fauna epigeica e edáfica de invertebrados em cultivos de mandioca consorciada com adubos verdes. O estudo foi realizado em cultivos de mandioca (M) em consórcios com feijão-de-porco (FP), milheto (MI) e guandu-anão (G), em comparação ao cultivo de mandioca tradicional (ST), sem a presença de adubos verdes. Os invertebrados epigeicos foram coletados com armadilhas de queda (pitfall) e os edáficos foram coletados de monólitos de solo. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
11
0
8
Order By: Relevance
“…Currently only 18 earthworm species from this biome are known, and some of them are well adapted to living in flooded soils (Carter & Beadle, 1931;. The data of the two studies carried out in this biome (Table 1 and Figure 2) showed that the earthworm populations there had a high density in native vegetation (Dias et al, 2006a), but a very low abundance under cassava (Manihot esculenta Crantz) crops (Brito et al, 2016). Unfortunately, the earthworm species were not identified, but it is known that flooded areas, including rice (Oryza sativa L.) plantations (Barrigossi et al, 2009;Bartz et al, 2009b), can harbor a significant numbers of native species, especially of the Ocnerodrilidae and Almidae families .…”
Section: Geographic Representation Of the Studiesmentioning
confidence: 99%
“…Currently only 18 earthworm species from this biome are known, and some of them are well adapted to living in flooded soils (Carter & Beadle, 1931;. The data of the two studies carried out in this biome (Table 1 and Figure 2) showed that the earthworm populations there had a high density in native vegetation (Dias et al, 2006a), but a very low abundance under cassava (Manihot esculenta Crantz) crops (Brito et al, 2016). Unfortunately, the earthworm species were not identified, but it is known that flooded areas, including rice (Oryza sativa L.) plantations (Barrigossi et al, 2009;Bartz et al, 2009b), can harbor a significant numbers of native species, especially of the Ocnerodrilidae and Almidae families .…”
Section: Geographic Representation Of the Studiesmentioning
confidence: 99%
“…Os predadores são muito importantes, pois controlam as populações de outros organismos no solo, especialmente a microbiota (BROWN et al, 2015). Nesse ponto de vista, Brito et al (2016) ressaltam ainda que a ocorrência do grupo Collembola pode contribuir indiretamente para o aparecimento do grupo Araneae, uma vez que estes se alimentam, dentre outros organismos, daqueles pertencentes à ordem Collembola (MOÇO et al, 2005).…”
Section: Gruposunclassified
“…Brown et al (1995), enfatizam que alterações em sua abundância e diversidade podem medir a perturbação do ambiente, apresentando respostas mais rápidas que outros atributos pedológicos. Neste sentido, vários foram os trabalhos desenvolvidos que utilizaram a fauna edáfica como indicadora da qualidade em diferentes condições de uso e manejo do solo (BRITO et al,. 2016;SANTOS et al, 2016;SCORIZA e CORREIA, 2016;RODRIGUEZ et al, 2016;CARVALHO et al, 2016;MARTINS et al, 2017).…”
Section: Epidhapic Fauna Influenced By Poultry Litter and Mineral Fodunclassified